Analysis and Evaluation of Radio Mobile Program on Line of Sight Paths, with Srtm and Aster Dteds and Its V11.6.6 / V9.1.6 Versions - Kaschel-Carcamo, H; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper is submitted as a continuation of a paper presented by the authors in IEEE-ACCA.- Concepción 2018, addresses an unexpected outcome on the propagation simulations on 24 Line of Sight TV links in Santiago, performed with last version of the freeware Radio Mobile and SRTM1 elevation data. Most of those links behave as having a high reflection level not consistent with the characteristic of the profiles involved.On a search for an answer, links and terrain parameters were deeply analyzed but still not explaining the discrepancies. Further analysis and simulations were performed involving ASTER, another compatible digital elevation data and later with a previous propagation model of Radio Mobile. Partial answers were obtained which are duly explained but still further work is required, including the author of Radio Mobile program. © 2019 IEEE.